Analisa Kualitas Layanan terhadap terhadap Kepuasan Nasabah di PT Bank Mandiri (Persero) Tbk. Cabang Sidoarjo Gedangan - Pierre Patarianto (Jurnal Maksipreneur, 2015)
This study aimed to analyze the quality of service on customer satisfaction in PT. Bank Mandiri (Persero) Tbk. Sidoarjo branch Gedangan, the variables used in this study was the quality of service consisting of Reability, responsiveness, assurance, empathy, and tangible as well as the level of customer satisfaction. This study was conducted to spread out questionnaires to 72 customers in the bank branch Gedangan Sidoarjo. To see the effect of service quality on customer satisfaction conducted sampling of respondents involved in the sampling process. Test equipment used is the technique of multiple linear regression analysis with SPSS 17.0 software. From the  results of multiple regression analysis in F test obtained Fhitung 22 285> of F Table of 2346 or by the significant value of 0000 in which the significance value is less than the significance level = 0.05. it can be concluded that Ho refused and Ha accepted, it means reliability (X1), responsiveness (X2) assurance (X3), empathy (X4), and tangible (X5) together have a significant impact on customer satisfaction (Y) , T test to determine the effect obtained partial realibility of 2611; variable responsiveness of 2155; variable assurance amounted to 2,383; emphaty variables for 4328; tangible variables for 2219. whose value is greater than ttable which amounted to 1,997, which means stating that the variable stress reliability (X1), responsiveness (X2), assurance (X3), empathy (X4), and tangible (X5), individually (partial) influence to variable customer satisfaction.